O patrocínio de empresas a clubes do futebol cearense: um estudo de caso - Bezerra, Fernando Clímaco Ferraro (2005)
The present study analyses, on its content the sports sponsorship made in two football teams of Ceará, the Ceará Sporting Club and the Fortaleza Sports Club, by four private enterprises, Construtora Mapec Ltda, Construtora Nossa Senhora de Fátima Ltda, Santana Têxtil do Brasil and Hapvida Lda, in the past ten years. Its main goal is to investigate the benefits that the sports sponsorship brought to the researched enterprises, the reasons that lead them to choose this kind of comunication media and if there was some sort of planning to its adoption. It searches, also, to identify if it had been any evaluation made by those organisations, relating to the return of the sports sponsorship, as also classify in wich step of the sponsorship development those enterprises are. It is talked about concepts, classifications, characteristics, planning, selection procedures and media goals. Analise the sides of sponsorship and of (mecenato) throught is history, concepts, nature, search of success, researches and evaluation. Justify, taking as basis the theorethycal inquires presented by several authors and the reason of the methodological aplication used. At the end, it evidences that the sports sponsorship of Ceará teams has developed as the years go by. Since the first studies, in the 1990 decade until today, the sponsorship enterprises stopped watching sponsorship as (mecenato), when doesn’t demand counter-strikes of its investments and started to understand that sports sponsorship could be used as an important way of media in order to reach its marketing aims, through the wide spread of its brand to the mass market. So it verifies with this study, that the sponsorship is used by enterprises as a marketing strategy, using it with sponsor actions in promotions, sales and institucional, expecting some return. Meanhile, those enterprises should develop better their sponsorship researches made in the Teams in order to have a wider and precise evaluation of the researched results, as a way to reach bigger counter-strikes of the invested money.